Tubeless & Stentless PCNL in Selected Cases Our Experience in Bangladesh - Bhuiyan, NI; Islam, MF; Khan, SA; Bhuiyan, ZH; Towhid, KMH; Ahmed, NIU; Salahuddin, K; Arafat, MA (Journal of Surgical Sciences, 2013)
Introduction: PCNL is well-accepted method of management of renal stone. In PCNL post operatively usually Nephrostomy tube and JJ stent are used. But Nephrostomy tube and JJ stent has some morbidity. Tubeless and JJ stentless PCNL in selected cases reduces the morbidity. This study will evaluate the results of PCNL with and without Nephrostomy tube and JJ stent in the management of renal stone in selected cases. Methods: From July 2008 to June 2010 total 70 cases of renal stone were managed by PCNL dividing into two groups Group A -PCNL with nephrostomy tube and JJ stent, Group B- Nephrostomy tubeless and JJ stent less PCNL with only ureteric catheter for 24 48 hour post operatively. All cases were operated in Urology department of Bangladesh Medical College Hospital, and two other private hospitals located in Dhaka. In all cases initially placed a ureteric catheter and at the end of the procedure compression at renal angle about 10 min in Group B, in Group A Procedure ended with Nephrostomy tube and JJ stent. Ureteric catheter was removed 24 hour-48 hour after operation. JJ stent was removed 3 weeks after operation. Exclusion criteria for the tubeless and JJ stentless approach were more than one percutaneous access, significant perforation of the collecting system, large residual stone burden, significant postoperative bleeding, ureteral obstruction and renal anomaly. The incidence of complication, length of hospitalization, analgesics requirement and interval to return to normal activities were evaluated. Results: All 70 percutaneous procedures were performed without significant complication, none of the patients demonstrated urinoma in postoperative renal Ultrasound scan. In Group- B length of hospital stay was < 3 days, the average analgesia requirement was 98 mg of Inj.Pethedin, patient return to normal activity earlier then Group -A. Conclusion: Nephrostomy tubeless and JJ stent less Percutaneous Nephrolithotomy with ureteric catheter for 24- 48 hours post operatively is a safe and effective procedure. Hospital stay and analgesia requirements are less and returns to normal activities are faster. DOI: http://dx.doi.org/10.3329/jss.v16i1.14443 Journal of Surgical Sciences (2012) Vol. 16 (1) : 18-25